Porphyromonas gingivalis-Induced NLRP3 Inflammasome Activation and Its Downstream Interleukin-1β Release Depend on Caspase-4 - Ding, Pei-Hui; Yang, Meng-Xin; Wang, Na-Na; Jin, Li-Jian; Dong, Yan; Cai, Xia; Chen, Li-Li (Frontiers in Microbiology, 2020)
Background: Oral commensals contribute to microbe-host symbiosis in periodontal homeostasis, and Porphyromonas gingivalis (P. gingivalis) as the keystone pathogen critically accounts for the shift of symbiosis to dysbiosis and periodontal destruction. NLRP3 (Nucleotide-binding oligomerization domain (NOD)-like receptor (NLR) family pyrin domain containing 3) inflammasome-mediated interleukin-1β (IL-1β) is significantly involved in periodontal diseases, and notably P. gingivalis enables to modulate the induction and expression of NLRP3. Whereas, the exact mechanism by which NLRP3 inflammasome is regulated in response to commensal and pathogenic bacteria remains unclear. Methods: To examine the expression of IL-1β and NLRPs inflammasome in tissues with severe chronic periodontitis, and further investigate how Caspase-4-dependent non-canonical NLRP3 inflammasome pathways functioned during the interactions of Streptococcus mitis (S. mitis) and P. gingivalis with human THP-1 cells. Results: IL-1β, NLRP3, NLRP6, NLRP12 and AIM2 inflammasome are highly expressed in gingival tissues with severe chronic periodontitis. In human THP-1 cells, P. gingivalis activates the synthesis and secretion of IL-1β to higher levels than S. mitis. Importantly, NLRP3-, Caspase-1-, and Caspase-4-siRNA knockdown THP-1 cells treated with P. gingivalis exhibited a lower expression level of IL-1β as compared to the control cells. In addition, silencing of either CASP4 or CASP1 can lead to a concurrent or reciprocal decrease in the expression of the other. Of note, the IL-1β induction is not affected in the S. mitis-treated THP-1 cells with the silence of NLRP3, Caspase-1 and Caspase-4 genes. Conclusion: NLRP3/Caspase-4 and NLRP3/Caspase-1 dependent IL-1β production may crucially contribute to the dysregulated immuno-inflammatory response in periodontal pathogenesis.